KARAKTERISTIK PUISI KARYA SISWA MTS NEGERI 1 PONTIANAK TAHUN PEMBELAJARAN 2015/2016 - Listiani, Isma; Sulissusiawan, Ahadi; Sanulita, Henny (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstractGeneral problem of the research was characteristics of poetry by students MTs Negeri 1 Pontianak in academic year 2015/2016. It was restricted into characteristics of students’ poetry which consists of diction, rhyme, theme and message. The purpose of this research was to describe aforementioned problem, whether the advantages of this research was be able to give knowledge and literature research development especially poetry produced by students and can be used as a teaching material for literature in school, becoming reference for the next research, and also becoming an effort to strengthen research in school. Based on the data analysis, (1) Diction used was leaning to concrete diction, connotation and loan elements, (2) rhyme that mostly used was broken rhyme. Another rhyme used were end rhyme, cross rhyme, middle, ereck, hugs and twins. (3) Theme which dominantly use was love for parents. Besides it, there were education, friendship, love for pets, divinity, environment and nationalism theme. (4) Message used in the students’ poetry was especially delivered for parents. In the entire of students’ poetry was mandated about death, social life, love for the only God,human relationships, man with nature, and the vertical relationship of man with his God. Keyword: Characteristic Poetry, Students’ Product.